Platyphyllenone Induces Autophagy and Apoptosis by Modulating the AKT and JNK Mitogen-Activated Protein Kinase Pathways in Oral Cancer Cells - Liu, Yen-Tze (Int J Mol Sci, 2021)
Platyphyllenone is a type of diarylheptanoid that exhibits anti-inflammatory and chemoprotective effects. However, its effect on oral cancer remains unclear. In this study, we investigated whether platyphyllenone can promote apoptosis and autophagy in SCC-9 and SCC-47 cells. We found that it dose-dependently promoted the cleavage of PARP; caspase-3, -8, and -9 protein expression; and also led to cell cycle arrest at the G2/M phase. Platyphyllenone up-regulated LC3-II and p62 protein expression in both SCC-9 and SCC-47 cell lines, implying that it can induce autophagy. Furthermore, the results demonstrated that platyphyllenone significantly decreased p-AKT and increased p-JNK1/2 mitogen-activated protein kinase (MAPK) signaling pathway in a dose-dependent manner. The specific inhibitors of p-JNK1/2 also reduced platyphyllenone-induced cleavage of PARP, caspase-3, and caspase -8, LC3-II and p62 protein expression. These findings are the first to demonstrate that platyphyllenone can induce both autophagy and apoptosis in oral cancers, and it is expected to provide a therapeutic option as a chemopreventive agent against oral cancer proliferation.